2000
DOI: 10.1038/sj.onc.1203972
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ErbB2 in cancer and ErbB2-targeting strategies

Abstract: This past decade has witnessed the remarkable advances in the understanding of the role of the erbB2 gene in cancers and the stunning progress in developing targeted therapies for erbB2-overexpressing cancers. Activation of the ErbB2 receptor signaling pathways can enhance various metastasis-associated properties that lead to an increase of cancer metastasis. Additionally, ErbB2 overexpression confers therapeutic resistance via receptor-mediated antiapoptotic signals. To limit these disastrous e ects of the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
313
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(320 citation statements)
references
References 66 publications
3
313
1
3
Order By: Relevance
“…HER2 is amplified and/or overexpressed in about 20-30% of cases of human breast cancer. HER2 overexpression correlates with large tumor size, tumor spread to lymph nodes, high grade, high percentage of S phase cells, aneuploidy, higher metastatic potential, and decreased survival, all consistent with an increase in the growth and metastatic potential of cancer cells (Yu and Hung, 2000). Blocking HER2 signaling arrests cancer cells in the G1 phase of the cell cycle and inhibits the growth of xenografts of tumors that overexpress HER2.…”
Section: Introductionmentioning
confidence: 69%
“…HER2 is amplified and/or overexpressed in about 20-30% of cases of human breast cancer. HER2 overexpression correlates with large tumor size, tumor spread to lymph nodes, high grade, high percentage of S phase cells, aneuploidy, higher metastatic potential, and decreased survival, all consistent with an increase in the growth and metastatic potential of cancer cells (Yu and Hung, 2000). Blocking HER2 signaling arrests cancer cells in the G1 phase of the cell cycle and inhibits the growth of xenografts of tumors that overexpress HER2.…”
Section: Introductionmentioning
confidence: 69%
“…This indicates that a clinically relevant concentration (5B200 nM) of paclitaxel is sufficient to kill E1A-expressing cells, but parental cells require much higher dosage, which may be difficult to be achieved in a clinical setting. 42 We have previously shown that Her-2/neu-overexpressing cells are resistant to paclitaxel-induced apoptosis 43,44 and E1A, through downregulation of Her-2/neu, can sensitize cellular response to paclitaxel-induced apoptosis. 22,23,43,44 In those studies, we could not detect E1A-mediated chemosensitization in the low Her-2/neu-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…42 We have previously shown that Her-2/neu-overexpressing cells are resistant to paclitaxel-induced apoptosis 43,44 and E1A, through downregulation of Her-2/neu, can sensitize cellular response to paclitaxel-induced apoptosis. 22,23,43,44 In those studies, we could not detect E1A-mediated chemosensitization in the low Her-2/neu-expressing cells. 22 The major reason for this discrepancy was due to the paclitaxel concentrations tested.…”
Section: Discussionmentioning
confidence: 99%
“…First, erbB2 alterations enhance the ability of a cancer cell to invade and metastasize. Second, overexpression of erbB2 is associated with an increase in therapeutic resistance to tamoxifen and some chemotherapeutic agents, such as methotrexate and paclitaxel (Yu and Hung, 2000). The erbB2 receptor is therefore an ideal target for breast cancer therapy.…”
Section: Introductionmentioning
confidence: 99%